Socio-Economic Impacts of Meleura Tourism Development on Employment, Income, and Community Welfare - Puspita Rizki, Dian (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2025)
This study examines the impact of the Meleura Tourism Site on employment opportunities, income levels, and community welfare in Lakarinta Village, Lohia District, Muna Regency. Although tourism development is often linked to local economic improvement, empirical evidence at the village level, particularly in coastal tourism areas, remains limited. This study employs a qualitative descriptive approach, with data collected through observation, in-depth interviews, and documentation. The findings indicate that tourism development has expanded employment in service and trade sectors and significantly increased household income. Average daily earnings rose from approximately IDR 30,000–50,000 before 2021 to IDR 150,000–300,000 during normal tourism seasons, with higher income during peak periods. Tourist arrivals increased steadily from 2,500 visitors in 2021 to 3,800 visitors in 2024, generating multiplier effects across microenterprises such as food stalls, boat rentals, and parking services. These developments have contributed to improved household welfare, stronger community participation, and enhanced local economic resilience. This study contributes to the literature on community-based tourism by providing empirical, village-level evidence of tourism’s socio-economic impacts. A key policy implication is the need for stronger regional government support in infrastructure development, capacity building, and facilitation of small enterprises to ensure sustainable and inclusive tourism growth.